Bacterial colonization due to increased nurse workload in an intensive care unit - Aycan,Ilker Onguc (2015)
INTRODUCTION: The rates of multiresistant bacteria colonization or infection (MRB+) development in intensive care units are very high. The aim of this study was to determine the possible association between the risk of development of nosocomial infections and increased daily nurse workload due to understaffing in intensive care unit. METHODS: We included 168 patients. Intensity of workload and applied procedures to patients were scored with the Project de Recherché en Nursing and the Omega scores, respectively. The criteria used for infections were those defined by the Centers for Disease Control. RESULTS: Of the 168 patients, 91 (54.2%) were female and 77 (45.8%) were male patients. The mean age of female and male was 64.9 ± 6.2 years and 63.1 ± 11.9 years, respectively. The mean duration of hospitalization in intensive care unit was 18.4 ± 6.1 days. Multiresistant bacteria were isolated from cultures of 39 (23.2%) patients. The development of MRB+ infection was correlated with length of stay, Omega 1, Omega 2, Omega 3, Total Omega, daily PRN, and Total PRN (p < 0.05). There was no correlation between development of MRB+ infection with gender, age and APACHE-II scores (p > 0.05). CONCLUSION: The risk of nosocomial infection development in an intensive care unit is directly correlated with increased nurse workload, applied intervention, and length of stay. Understaffing in the intensive care unit is an important health problem that especially affects care-needing patients. Nosocomial infection development has laid a heavy burden on the economy of many countries. To control nosocomial infection development in the intensive care unit, nurse workload, staffing level, and working conditions must be arranged.